Pelatihan Machine Learning Menggunakan Bahasa Pemrograman Python Bagi Karyawan PT. Yokogawa Indonesia - Santoso, Handri; Rochadiani, Theresia Herlina (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Industry 4.0 insists companies to apply intelligent application technology to their industries. Machine learning as one of field of Artificial Intelligence has used widely in Smart Factory, such as to detect product defects, to predict potential problems and for its solutions. PT. Yokogawa Indonesia, one of global company, wanted to prepare its employees to implement Smart Factory, as its response for Industry 4.0 and competition with other companies. As a solution to this problem, the community service held machine learning training using Python for PT. Yokogawa Indonesia’s employees. The training was held once a week for five weeks. Interaction and discussion online between trainer and participants used Teams Microsoft application. It also used google classroom for managing materials and assignments during this training. More than 50% of participants never learn machine learning before this training. In the last session of the training, questionnaire was given to the participants. As the result, a half of total of participants agreed that their knowledge about machine learning has increased significantly through this training.